Circadian and sex differences in carotid-femoral pulse wave velocity in young individuals and elderly with and without type 2 diabetes - Gentilin, Alessandro; Moghetti, Paolo; Cevese, Antonio; Mattioli, Anna Vittoria; Schena, Federico; Tarperi, Cantor (Frontiers in Cardiovascular Medicine, 2022)
The incidence of cardiovascular events is higher in the morning than in the evening and differs between sexes. We tested the hypothesis that aortic stiffness, a compelling cardiovascular risk factor, increases in the morning than in the evening in young, healthy individuals between 18 and 30 years (H18–30) or in older individuals between 50 and 80 years, either healthy (H50–80) or with type 2 diabetes (T2DM50–80). Sex differences were also investigated. Carotid-femoral pulse wave velocity (cf-PWV) recorded via Doppler Ultrasound, blood pressure and heart rate were checked at 6 a.m. and 9 p.m., at rest and during acute sympathetic activation triggered by handgrip exercise. Cf-PWV values were lower in the morning compared to the evening in all groups (p < 0.01) at rest and lower (p = 0.008) in H18–30 but similar (p > 0.267) in the older groups during sympathetic activation. At rest, cf-PWV values were lower in young women compared to young men (p = 0.001); however, this trend was reversed in the older groups (p < 0.04). During sympathetic activation, the cf-PWV was lower in women in H18–30 (p = 0.001), similar between sexes in H50–80 (p = 0.122), and higher in women in T2DM50–80 (p = 0.004). These data do not support the hypothesis that aortic stiffness increases in the morning compared to the evening within any of the considered groups in both rest and sympathetic activation conditions. There are differences between the sexes, which vary according to age and diabetes status. In particular, aortic stiffness is higher in older women than in men with diabetes during acute stress.